Effects of three kinds of Chinese herbs on growth performance, oocysts output and gut microbiota in growing lambs with coccidiosis - He, Yanfeng; Wang, Zhanming; Li, Shijie; Chen, Pan; Liu, Kaili; Li, Manman; Wang, Yingmin; Shaukat, Aftab; Abdullah, Muhammad; Li, Senyang; Huang, Shucheng; Jian, Fuchun (Folia parasitologica, 2024)
Coccidiosis is a protozoan intestinal disease that reduces the production of the sheep industry and causes large economic losses for sheep. Although chemically synthesised drugs are routinely employed to treat coccidiosis in sheep, the anticoccidial drug resistance and drug residues in edible meat have prompted an urgent search for alternatives. Herein, the anticoccidial properties of diclazuril, a conventional anticoccidial drug, and Allium sativum, Houttuynia cordata and Portulaca oleracea were assessed. Forty 45-day-old lambs naturally infected with Eimeria spp. were selected and randomly divided into five groups. The results showed that the sheep treated for coccidiosis had considerably decreased average daily gain (ADG) during both administration and withdrawal of the drug compared to the control group. Furthermore, at days 14, 21, 28 and 35, respectively, the three herbs and diclazuril had similar anticoccidial effects, with lower oocysts per gram (OPG) than the control group. On day 78, OPG in the three herbal groups was significantly lower than in the diclazuril group. In addition, the abundance and composition of the gut microbiota were changed in sheep treated with the three herbs and diclazuril compared to the untreated sheep. Moreover, some intestinal microorganisms have a correlation with OPG and ADG when using Spearman correlation analysis. In summary, our results suggest that all three herbs produce anticoccidial effects similar to diclazuril and modulate the balance of gut microbiota in growing lambs.
Keywords: Drugs, Chinese Herbal; Animals; Gastrointestinal Microbiome; ovce; oocysty; Oocysts; Eimeria; Epizootiology; kokcidióza; Coccidiosis; sheep; Triazines; léky rostlinné čínské; nemoci ovcí; microbiome; střevní mikroflóra; Sheep; prevention and treatment; triaziny; zvířata; kokcidiostatika; Coccidiostats; Sheep Diseases